Tlingit totem poles, Tuxekan, Alaska, ca. 1904 - Case, W. H. (William Howard), 1868-1920
Seven Tlingit totem poles, Tuxekan, Alaska, ca. 1891-1910. Caption on image: Totems at Old Tuxekan Village. W.H. Case 176-N Notes from unidentified sources: Henya tribe of Tlingit PH Coll 300.37